Proximity to Power and Jewish Sectarian Groups of the Ancient Period : A Review of Lifestyle, Values, and Halakha in the Pharisees, Sadducees, Essenes, and Qumran - Newman, Hillel, (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
This book deals with the values, lifestyle and code of law of four Jewish sectarian groups in the Hellenistic and Roman (Second Temple) period, in the land of Israel. It reviews the groups according to their proximity to power, highlighting the fact that political involvement has a decisive impact on the life and development of these social groups. The groups under review, the Pharisees, Sadducees, Essenes and Qumran, receive a new historical description, from the viewpoint of their proximity to power. The issue of what determines the course of a social group, whether normative or sectarian, is discussed, and the traditional terminology is re-examined. Original terminology is established. The first part of the book deals with the question of terminology, the available sources and the presentation of the different groups.